PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP KELENGKAPAN PENGUNGKAPAN LAPORAN KEUANGAN PADA PERUSAHAAN FOOD AND BEVERAGES - Bosar Hasibuan (Universitas Riau Kepulauan, 2016)
The purposes of this study is to provide empirical evidence about the effects of company leverage and liquidities on the comprehensiveness of disclosure in financial reports of food and beverages companies listed in Indonesia Stock Exchange in the period 2010-2012. Data used in this study is secondary data, financial and annual reporting 2010-2012 from Indonesia Stock Exchange. The population of this study are food and beverages companies listed in Indonesia Stock Exchange from 2010-2012 were obtained from the publication of the Indonesia Stock Exchanges by the web www.idx.co.id. The samples of this study are 14 companies in three years, total are 42 annual financial reports of food and beverages companies. The sample drawn by purposive sampling and fulfill sample selection criterion. The mandatory disclosure index consisting of 86 mandatory items was developed to measure the level of mandatory disclosure in financial reports.Analysis techniques used in this study is the method of multiple linear regression and hypothesis testing F-statistic to test the effect together with a significant level of 5% and using the t-statistic for testing the partial regression coefficients. In the classical assumption test results showed that there were no irregularities classical assumption, this suggests that the available data has been qualified to use multiple linear regression model. These results indicate that Simultaneous F-test showed that the debt to equity ratio and current ratio have a significant effect on the disclosure comprehensiveness of the financial statements, the variable debt to equity ratio (DER) has not significant negative effect and current ratio has a significant positive effect on the disclosure comprehensiveness in financial statements. Regression equation obtained is The Disclosure Comprehensiveness = 0.694 + -0.004DER + 0.015CR. The coefficient of determination R2 is 14.4% which means that 14.4% the disclosure comprehensiveness is affected by independent variables are debt to equity ratio (DER) dan current ratio (CR), while the remaining 85.6% is influenced by other variables not examined in this study.